Closure of the anterior and posterior fontanelle in the New Zealand population: A computed tomography study. (12th October 2018) - Kirkpatrick, Joshua; Bowie, Sarah; Mirjalili, Seyed A
Abstract : Aim: Significant ethnic variation has been demonstrated in the closure of the anterior fontanelle (AF); however, to date, this has not been investigated in the Māori/Pasifika population. Methods: The computed tomography scans of 163 individuals (116 Māori/Pasifika and 47 New Zealand (NZ) European) aged between birth and 4 years were retrospectively analysed to investigate the surface area (SA) and time of closure of the anterior and posterior fontanelles in New Zealand. Results: The Māori/Pasifika group showed clinical AF closure (SA < 114 mm 2 ) rates of 25% at 4–6 months, increasing to 47% at 10–12 months and 80% at 13–18 months. The posterior fontanelle was clinically unfused in 17% of the Māori/Pasifika group aged <1 month and in 7% of the 1–3‐month‐old group. No cases of posterior fontanelle non‐fusion were identified in the NZ European population. Conclusion: This study establishes normal values for AF size and closure frequency for the first time in the paediatric Māori/Pasifika population.